ANALISIS PERMINTAAN BUAH SEMANGKA DI KOTA PALANGKA RAYA - Julkifli, Julkifli; Maleha, Maleha; Rajudinnor, Rajudinnor (JOURNAL SOCIO ECONOMICS AGRICULTURAL, 2019)
This study aims to determine the factors that influence the demand for watermelon in the City of Palangka Raya. The data used are secondary data from 2002-2016. Data analysis method is multiple linear regression analysis using SPPS-24 tool. The results showed that the coefficient of determination was 0.936, meaning 93.6% of the demand for watermelon in Palangka Raya City was influenced by the price of watermelon, the price of papaya fruit, the price of bananas, per capita income and population. The results of the F test show that the calculated F = 26.109 is greater than the Ftable value = 6.06 at the 99% confidence level, so that the factors tested together have a significant effect on the demand for watermelon in the City of Palangka Raya that is at the level of trust of 90%-99%. While the population factor has no effect on the 95% confidence level.